Transition risk and firm level impact - Jánska, Zuzana (2025)
This thesis explores how firms can assess and disclose the financial effects of climate-related transition risks in accordance with European Sustainability Reporting Standards’ disclosure requirement E1-9 Anticipated financial effects from material physical and transition risks and potential climate-related opportunities. Using and adjusting corporate model developed by Emambakhsh et al. (2023), the financial impacts of transition risk are analyzed for company EP Infrastructure a.s. using two climate scenario sets. The analysis reveals limited negative effects of the climate-related transition risk on the company's financial performance. The model and the results are compared with the company's own disclosure to assess variations in methodology, scope, and compliance with regulatory requirements. Based on the results of the analysis the thesis attempts to solve practical problems that firms face, like resource and data limitations by providing a theoretical guideline on European Sustainability Reporting Standards’ requirements, firm agnostic recommendations and a resource-efficient approach as a feasible solution for businesses looking to comply with new sustainability reporting demands.